The Relationship Between Sleep Quality and Hemoglobin Levels in Third-Trimester Pregnant Women - Nur Mufida Alfi; Nur Anisafauziah Ilham; Cici Noval (Minsight: Midwifery Insight and Innovation Journal, 2026)
Sleep quality during pregnancy plays an important role in maternal health, particularly in the third trimester when physiological and psychological changes increase significantly. Poor sleep quality may affect hemoglobin levels and contribute to anemia among pregnant women. This study aimed to determine the relationship between sleep quality and hemoglobin levels in third-trimester pregnant women. This research used an analytical observational design with a cross-sectional approach. The study involved third-trimester pregnant women who attended antenatal care services at a selected health center (N=47). Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while hemoglobin levels were obtained through laboratory examination. Data were analyzed using the Spearman correlation test with a significance level of p<0.05. The results showed that most respondents experienced poor sleep quality and had mild to moderate anemia. Statistical analysis indicated a significant relationship between sleep quality and hemoglobin levels among third-trimester pregnant women (p=0.000), where poorer sleep quality was associated with lower hemoglobin levels. These findings suggest that improving sleep quality may help maintain adequate hemoglobin levels during pregnancy. Therefore, healthcare providers should include sleep quality assessment and education as part of routine antenatal care services.